Factors Influencing the Development of English Language Listening and Reading Skills of Public Primary School Pupils: A Case Study of Temeke Municipality, Tanzania - Rehema John; Prospery M. Mwila (PT. Pusmedia Group Indonesia, 2025)
Because many of the courses taught and class assignments assigned need reading comprehension, successful students in school are those who acquire an interest in listening and reading. The purpose of the study was to determine factors influencing the development of English Lamguage Listening and Reading skills among public primary schools in Temeke Municipality in Kinondoni, Dar es Salaam, Tanzania. Two objectives were employed to guide the study, namely, to investigate the availability of teaching resources for reading and listening skills in English and to identify other factors affecting pupils’ attainment of listening and reading skills in English. The study employed a mixed-methods design and a convergent parralle design. Five hundred and fifty (550) participants, including head teachers, teachers and pupils, were sampled through probability and nonprobability sampling techniques. Interview guides, questionnaires and classroom observation guides were used as tools for data collection. The results revealed that the majority of teachers in public primary schools lacked adequate command of the methods, strategies, and stages for teaching reading skills. Other factors that influenced the teaching of reading skills in public primary schools and thus the acquisition of reading skills included an insufficient number of qualified teachers, overcrowding of pupils in one class, a lack of textbooks, supplementary books, and other reading materials, pupil truancy, regular curriculum changes without proper teacher training on the changes, and a failure of pupils to attend preprimary school education. As a result of these deficiencies, it was discovered that the capacity to teach reading skills in public primary schools varied from one school to the next as well as among teachers within the same schools. The study recommended that short courses on teaching methodology should be held in teachers' resource centers to train teachers on the methods, tactics, and procedures involved in teaching reading skills.